2007
DOI: 10.1128/iai.01107-06
|View full text |Cite
|
Sign up to set email alerts
|

A Caspase-Independent Pathway Mediates Macrophage Cell Death in Response toMycobacterium tuberculosisInfection

Abstract: Macrophages can undergo apoptosis after infection with Mycobacterium tuberculosis. This macrophage response deprives the bacillus of its niche cell and supports the host response through better antigen presentation. The intracellular pathways of apoptosis that elaborate this macrophage response are not well understood. To address this issue, we investigated the contribution of various apoptosis pathways to M. tuberculosis-induced macrophage cell death. We found that macrophages die in a caspase-independent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 49 publications
9
82
2
Order By: Relevance
“…Although our observation of cathepsin B dependency in M. tuberculosis-and M. marinum-induced cell death and inflammasome activation is novel, involvement of lysosomal proteases in Mycobacterium-induced cell death is not unprecedented, as Lee and colleagues (40) previously showed that lysosomal cathepsin inhibitors prevented murine macrophage cell death caused by infection with M. tuberculosis H37Rv. By contrast, lysosomal cathepsins have also been reported to be dispensable for macrophage cell death after M. tuberculosis infection (41). A role for cathepsin B in inflammasome activation has also been observed for some Gram-negative pathogens (43)(44)(45).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although our observation of cathepsin B dependency in M. tuberculosis-and M. marinum-induced cell death and inflammasome activation is novel, involvement of lysosomal proteases in Mycobacterium-induced cell death is not unprecedented, as Lee and colleagues (40) previously showed that lysosomal cathepsin inhibitors prevented murine macrophage cell death caused by infection with M. tuberculosis H37Rv. By contrast, lysosomal cathepsins have also been reported to be dispensable for macrophage cell death after M. tuberculosis infection (41). A role for cathepsin B in inflammasome activation has also been observed for some Gram-negative pathogens (43)(44)(45).…”
Section: Discussionmentioning
confidence: 94%
“…Previous infection studies with M. tuberculosis strain H37Rv showed that cathepsin B and L inhibitors reduced DNA fragmentation and macrophage cell death, suggesting the involvement of lysosomal proteases in Mycobacterium-induced cell death (40,41). In this study, we investigated a possible role for lysosomal proteases cathepsin B, D, and L in M. marinum-induced cell death.…”
Section: A Nonapoptotic M Marinum-induced Cell Deathmentioning
confidence: 99%
“…A serine protease inhibitor appears to block this caspase-independent death. 102 Moreover, at high multiplicity of infection (MOI), M. tuberculosis induces a caspaseindependent cell death that is not observed at low MOI. 103 In the case of Shigella, the primary death mode is pyroptosis, induced through the Ipaf-caspase-1 inflammasome.…”
Section: Caspase-independent Cell Death: Oncosis and Pyronecrosismentioning
confidence: 99%
“…As shown in Figure 6E, 3-MA could partially reverse cell death, which suggested that the 4'-chloro-3,5-dihydroxystilbene-induced cell death was partially mediated by autophagy. Furthermore, we used various protease inhibitors to analyze whether cell death was caused by an acidic lysosomal protease [19,20] . As shown in Figure 6E, two cathepsin inhibitors (CA074-Me and Z-FA-FMK), two serine protease inhibitors (TLCK and AEBSF) and one proteasome inhibitor (MG132) could not prevent cell death; only one serine protease inhibitor, TPCK, slightly reversed cell death.…”
Section: Resultsmentioning
confidence: 99%